Questioning Skills, Critical Thinking Ability, and Emotional Maturity in Relation to Students’ Learning Outcomes in Primary Schools - Emi Lestari; Suriswo Suriswo; Dewi Apriani (Journal of Educational Sciences, 2026)
This study examines the relationship between questioning skills, critical thinking ability, and emotional maturity and their influence on the learning outcomes of first-grade students at SDN 2 Kebondalem, Pemalang. The study was conducted because students’ academic achievement is not only shaped by cognitive competence but also emotional development. The purpose of this research was to determine the partial and simultaneous effects of these three variables on students’ learning outcomes. A quantitative correlational design with an ex post facto approach was applied, involving all 84 students as participants. Data were collected through validated and reliable questionnaires measuring questioning skills, critical thinking ability, and emotional maturity, while learning outcomes were obtained from academic records. Multiple linear regression analysis was performed using SPSS 23 after meeting classical assumption tests. The findings show that questioning skills, critical thinking ability, and emotional maturity each have a significant effect on students’ learning outcomes, both individually and simultaneously. The study concludes that strengthening inquiry-based learning and emotional competence is essential to enhance academic performance in primary education.